Implementasi Project-Based Syllabus dalam Meningkatkan Mutu Pembelajaran - I Dewa Gede Rat Dwiyana Putra (UHN IGB Sugriwa Denpasar, 2016)
One of the important components which determine the quality of education is the quality of instructional process. A qualified instructional process is characterized by the involvement of all instructional aspects, namely; human resources, material, media, and also the environment where the instructional process takes place, (Mukhid, 2007). All of those instructional aspects need to be accommodated by an appropriate method in order to make them effective. An instructional method that is proved effective in improving the instructional process is Project-Based Learning (PBL). This method of teaching and learning would facilitate the students with the instructional process that accommodate the students’ creativity and potentials. PBL provides authentic challenges and choices of processes in accomplishing the task. The teacher guides the students as a facilitator while the students do the project using their individual initiative. Moreover, individual initiative which is different in every student then empowers the team work to get the expected goal (Liegel, 2004). Finally, the instructional syllabus should first be constructed to implement PBL effectively that could accommodate all of its advantages. This article would elaborates the application of EFL syllabus that is made based on PBL method. The syllabus was applied in Applied English Class of Religious Education Department, IHDN Denpasar. The findings highlight both benefits and shortcomings of this type of syllabus and also emphasize the importance of Project-Based Syllabus in improving the quality of instructional process.